ANALISIS DAYA DUKUNG IZIN PONDASI SUMURAN PADA JEMBATAN SUNGAI PANGI KABUPATEN MERANGIN - Melia Juniza; M Nuklirullah; Dila Oktarise Dwina (JMTS: Jurnal Mitra Teknik Sipil, 2022)
This study aims to analyze the bearing capacity of the foundation permit for the Sungai Pangi bridge. The well foundation will be analyzed in the form of permit carrying capacity which will be compared with the load working on it. The Sungai Pangi Bridge in Merangin Regency is a concrete bridge that is included in the class C bridge, the total length of the bridge is 41,1 meters. The span of the bridge at the foundation point under consideration is 15 meters long. The maximum load acting on the foundation is 4332,09 kN. This bridge uses a type of well foundation with varying depths. The analysis of the calculation of the bearing capacity of the foundation uses three methods, namely the Direct Method with the result of the permit carrying capacity of 13121,8 kN, the Price & Wardle method with the result of the permit carrying capacity of 6880.87 kN and the Philipponant Method with the result of the permit carrying capacity of 7614,34 kN. The three methods used in calculating the permit load analysis, have a permit carrying capacity value that meets the requirements for safe foundations, where the value of the bearing capacity of the foundation permit is greater than the load received by the foundation.   Abstrak Penelitian ini bertujuan untuk menganalisis daya dukung izin pondasi sumuran jembatan Sungai Pangi. Pondasi sumuran akan dilakukan analisis berupa daya dukung izin yang nantinya akan dibandingan dengan beban yang bekerja diatasnya. Jembatan Sungai Pangi Kabupaten Merangin merupakan jembatan beton yang termasuk pada jembatan kelas C, panjang total jembatan 41,1 meter. Bentang jembatan pada titik pondasi yang ditinjau adalah sepanjang 15 meter. Beban maksimum yang bekerja pada pondasi adalah sebesar 4332,09 kN. Jembatan ini menggunakan jenis pondasi sumuran dengan kedalaman bervariasi. Analisis perhitungan daya dukung pondasi menggunakan tiga metode yaitu Metode Langsung dengan hasil daya dukung izin sebesar 13121,8 kN, Metode Price & Wardle dengan hasil daya dukung izin sebesar 6880,87 kN dan Metode Philipponant dengan hasil daya dukung izin sebesar 7614,34 kN. Ketiga metode yang digunakan dalam perhitungan analisis beban izin memiliki nilai daya dukung izin yang memenuhi syarat aman pondasi, yang mana nilai daya dukung izin pondasi lebih besar dibandingkan beban yang diterima oleh pondasi.